Faculty Publications from a Research University: The Scholarly Impact of Open Access versus Non-Open Access. Issue 2 (3rd April 2017) - Salisbury, Lutishoor; Chowdhury, Anuradha Rai; Smith, Jeremy J.
ABSTRACT: We used the faculty publications published in fully open access and non-open access journals that are indexed in the Web of Science core collections to study the extent our researchers are publishing in these fully open access journals and to identify the relative impact of their open access (OA) versus non-OA publications, to identify their h -indexes, and to explore the citation advantages. Overall, the average citation is higher for non-OA papers. When the data were examined by year of publication, citations were higher for non-OA papers six of the eleven years under study. The other years show no citation advantage. On examination of the science and technology material in the Web of Science and Google Scholar databases, the field of physics had a citation advantage for non-OA articles for all the years under study, and in entomology, except for one year, non-OA also had a citation advantage. For biological sciences, in Web of science, five of the eleven years OA citations were higher, and in Google Scholar for all years OA had a citation advantage. For papers published in 2014 and 2015, there was no citation advantage for the majority of articles in both groups.